Improvement of existing water quality index in Selangor, Malaysia. - Al-Mamun, Abdullah; Hafizah, Nor; Alam, Md. Zahangir (2009)
A reviesd and improved water quality index (WQI) is proposed for the State of Selangor in Malaysia. Analyses were conducted to develop the rating curve, find the new subindices and weighing factors for the selected parameters. The water quality parameters were grouped according their similarities. The class of water gained at 1K07 (Klang River station) using new WQI equation and existing WQI equation was Class IV and Class III respectively. However, the statuses of the water for both cases were the same, where both of them were classified as polluted water. In other case, for example at 1L02 (Langat River station), the class resulted from the new and existing WQI was the same. But, the status of the water was different, where the new WQI indicated that the water was clean, while the existing WQI indicated that the water was slightly polluted. The proposed WQI seemed to be slightly more strict compared to the existing one, which is thought to bring benefit the river environment. The outcomes of this research can be applied to protect the rivers in Selangor.